The confidence to speak: Measuring impacts of a community leadership program on community leadership skills and self-identification. Issue 1 (1st January 2022) - Prado, Carolina; Cushing, Kathering; Figueroa, Elizabeth; Rodriguez, Imelda; Pelagio, Mayra; Castro, Marisela
ABSTRACT: This case study explores the participant perspectives of a Community Leadership Program (CLP) in an underserved community. The CLP aimed to improve community conditions by increasing participants' knowledge, skills, and confidence to participate in local governance forums. Our three research foci were to understand (1) how successful the program was in building individual leadership skills, (2) how skills were applied through participation in leadership activities, and (3) identify the barriers for practicing leadership in marginalized communities. Findings show that CLP participants highlighted the program's impact on their: confidence to express their findings in public, ability to outreach to members of their community, and self-identify as leaders. While participants were participating more in social and political activities, they also expressed that the program did not equip them to deal with serious barriers such as responses to community members' practice of leadership, access to institutional power and knowledge, and lack of resources.